1999
DOI: 10.1016/s0002-9440(10)65160-7
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Receptor Expression in Prostate Cancer and Premalignant Prostatic Lesions

Abstract: Estrogens have been implicated in prostatic cancerogenesis and tumor progression. The mechanisms underlying estrogen signaling in human prostate tissue, however, remain poorly understood. Using immunohistochemical and in situ hybridization (ISH) techniques, the present study demonstrates the classical estrogen receptor (ERalpha) in premalignant lesions and prostatic adenocarcinoma through the various stages of the disease. Conversely, the novel characterized ERbeta subtype was undetectable in human prostate ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
185
1
13

Year Published

2000
2000
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 211 publications
(222 citation statements)
references
References 35 publications
17
185
1
13
Order By: Relevance
“…Another mode of RAC 3 activity in prostate cancer cells may be via its well characterised interaction with the ER (Anzick et al, 1997;Tikkanen et al, 2000;Xu et al, 2000). The oestrogen receptor (ER) has been shown to be present in human prostate cancer and pre-malignant lesions (Bonkhoff et al, 1999), while the prostate cell lines LNCaP, DU 145 and PC 3 have been shown to express the β isoform of the receptor (Lau et al, 2000). From these studies, ER status appears to be an important factor in prostate cancer progression.…”
Section: Discussionmentioning
confidence: 99%
“…Another mode of RAC 3 activity in prostate cancer cells may be via its well characterised interaction with the ER (Anzick et al, 1997;Tikkanen et al, 2000;Xu et al, 2000). The oestrogen receptor (ER) has been shown to be present in human prostate cancer and pre-malignant lesions (Bonkhoff et al, 1999), while the prostate cell lines LNCaP, DU 145 and PC 3 have been shown to express the β isoform of the receptor (Lau et al, 2000). From these studies, ER status appears to be an important factor in prostate cancer progression.…”
Section: Discussionmentioning
confidence: 99%
“…Thus it was proposed that ERα may have a tumor suppressor role in the prostate gland and loss of its expression may be an early event in prostatic disease. Interestingly, ERα expression has been observed in some prostate cancer cell lines [86] as well as in hormone refractory and metastatic lesions suggesting its re-emergence as cancer progresses [87] although this has not been consistently seen in all studies [88]. It is also noteworthy that prostate cancer risk has been associated with genetic polymorphisms in the ERα gene particularly within Japanese and African American populations implicating a potential causal relationship between ERα mediated estrogenic action and prostate cancer [89,90].…”
Section: Erαmentioning
confidence: 99%
“…130 Prostate-specific membrane antigen, an abundant transmembrane glycoprotein, shows increased expression in PIN and cancer when compared with benign epithelium, 131,132 and this expression was unaffected by short-term androgen deprivation therapy. 132 Estrogen receptor alpha is present in up to 28% of cases of PIN and 43% of cancers, but estrogen receptor beta is absent; 133 prolactin receptor expression is increased in PIN. 134 A model of prostatic carcinogenesis has been proposed based on the morphologic continuum of PIN and the multistep theory of carcinogenesis.…”
Section: Genetic and Molecular Changesmentioning
confidence: 99%